METHODS OF THE LIE DETECTION FOR STUDENTS WITH DIFFERENT LEVEL OF THE EMOTIONAL INTELLIGENCE - Vasiuk, Katerina; Bozhneko, Vladislava (PSYCHOLOGICAL JOURNAL, 2017)
Lie detection, the issue of the day in modern psychology, is analyzed in this article. Particularly, one of its types - non-instrumental detection - is discussed. The results of the examination of modern researches concerning effective ways of its detection, generalized diagnostic criteria which are used for detection in psychology are provided in the article. The main criteria used for experimental research can be described as: non-verbal-kinesthetic (facial expressions, gestures and postures), eye’s moves, vegetative indicators (face redness, tremor), paralinguistic signs (tone and timbre of voice, pauses, rate of speech), and also verbal means (grammar structure of the text and tirades). It was assumed that the success in lie detection depends on the level of emotional intelligence of a person because people with high level of emotional intelligence recognize and understand emotional condition of others way better. However, this assumption was not proved. People with high level of emotional intelligence evaluated their abilities to detect lie higher, however, in practice, they showed lower results because they relied on their own impressions and intuition rather than rational analysis. It was experimentally proved that the success in detection does not depend on the level of emotional intelligence but those means which person chooses for lie detection. Those methods which rely on text examination (tirades, pauses, language mistakes) are especially effective, on the contrary, non-verbal indicators (gestures and facial expressions) proved to be ineffective.